(untitled) (Zien Journal of Social Sciences and Humanities, 2021)
Scientific expeditions organized in the 1920s dealt with the problems of the productive forces of the lower reaches of the Amu Darya, irrigation, transport, fishing, and animal husbandry. In 1925, L.S. Berg organized a scientific expedition to the Aral Sea basin, the purpose of which was to study fisheries, fishing gear, species and stocks of fish and conditions of navigation in the Aral Sea.